REPRODUCTIVE HEALTH IN THE CONTEXT OF HEALTH PROMOTING UNIVERSITY (HPU) - Shilvi Khusna Dilla Agatta; Chusna Cahya Marhaeni; Irmayani Said (Jurnal Analisa Sosiologi, 2025)
Reproductive health is often narrowly framed around menstruation, childbirth, and pregnancy, reflecting a patriarchal view of women’s bodies as production tools. In Indonesia, public health behaviors remain below optimal standards, necessitating strategic health promotion efforts. As centers of knowledge production, universities hold significant potential to advance public health education, particularly for younger generations. One such initiative, Menuju Kampus Sejahtera, aims to disseminate reproductive health information and promote a holistic, gender-inclusive understanding. However, the content still predominantly centers on women’s health, reinforcing gendered assumptions. This research employs Michel Foucault’s theory of biopolitics to analyze how power operates through biological regulation, especially via medicalization where medical discourse is used to shape and control individual behaviors. The study uses a qualitative method with a reflexive ethnographic approach to explore how reproductive health narratives are shaped, internalized, and challenged within the university setting. Data was gathered through literature studies and in-depth interviews with students who had engaged with the HPU platform. Reflexivity and positionality were used to address ethical and interpretative dimensions, particularly when dealing with sensitive topics. By critically examining the content and framing of campus health promotion programs, the research highlights the limitations of current narratives and calls for more inclusive approaches that address reproductive health beyond traditional gender binaries. This study contributes to the sociological understanding of how health knowledge is produced, distributed, and experienced in higher education settings, and proposes a gender-transformative framework for reproductive health promotion.